Skeletal muscle-specific overproduction of constitutively activated c-Jun N-terminal kinase (JNK) induces insulin resistance in mice - Henstridge, D. C. (2012)
AIMS/HYPOTHESIS: Although skeletal muscle insulin resistance has been associated with activation of c-Jun N-terminal kinase (JNK), whether increased JNK activity causes insulin resistance in this organ is not clear. In this study we examined the metabolic consequences of isolated JNK phosphorylation in muscle tissue. METHODS: Plasmids containing genes encoding a wild-type JNK1 (WT-JNK) or a JNK1/JNKK2 fusion protein (rendering JNK constitutively active; CA-Jnk) were electroporated into one tibialis anterior (TA) muscle of C57Bl/6 mice, with the contralateral TA injected with an empty vector (CON) to serve as a within-animal control. RESULTS: Overproduction of WT-JNK resulted in a modest (~25%) increase in phosphorylation (Thr(183)/Tyr(185)) of JNK, but no differences were observed in Ser(307) phosphorylation of insulin receptor substrate 1 (IRS-1) or total IRS-1 protein, nor in insulin-stimulated glucose clearance into the TA muscle when comparing WT-JNK with CON. By contrast, overexpression of CA-Jnk, which markedly increased the phosphorylation of CA-JNK, also increased serine phosphorylation of IRS-1, markedly decreased total IRS-1 protein, and decreased insulin-stimulated phosphorylation of the insulin receptor (Tyr(1361)) and phosphorylation of Akt at (Ser(473) and Thr(308)) compared with CON. Moreover, overexpression of CA-Jnk decreased insulin-stimulated glucose clearance into the TA muscle compared with CON and these effects were observed without changes in intramuscular lipid species. CONCLUSIONS/INTERPRETATION: Constitutive activation of JNK in skeletal muscle impairs insulin signalling at the level of IRS-1 and Akt, a process which results in the disruption of normal glucose clearance into the muscle.